Hegemony of Penghulu in Tor-Tor Raja-Raja Dance in Jorong Silayang Ranah Batahan Sub-District West Pasaman District - Fitrah Hayati; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
The purpose of this research is to describe and analyze the presence of penghulu in Tor-Tor Raja-Raja dance and describe the reasons for the presence of penghulu in Tor-Tor Raja-Raja dance. This type of research is qualitative research with descriptive method. The object of this research is the headman in Jorong Silayang. The data used in this research are primary data and secondary data. The main instrument in this research is the researcher himself assisted by supporting instruments such as cameras, stationery, and cellphones. Data collection techniques are done by means of literature study, observation, interviews and documentation. The results showed that Tor-tor Raja-raja dance is a traditional dance in Silayang jorong which is performed by the community in a wedding party in Silayang jorong and can only be danced by penghulu. Penghulu in the Silayang area has a dominant influence in the Tor-tor Raja-raja dance, because it is the penghulu who decides in the wedding ceremony whether the Tor-tor Raja-raja dance can be performed or not. The reason the Tor-tor Raja-raja dance itself cannot be danced by other than the penghulu is because the penghulu in Jorong Silayang inherited the rules made by the previous kings.